Employee Skills Development through Job Training Programs at PT Pos Indonesia (Persero) Kediri Branch - Nuzula, Mohamad Firdausyi; Dewani, Shinta Laura (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2024)
One crucial factor in achieving organizational goals is human resources (HR). Efforts to develop skills through job training are necessary to maximize HR performance. This study aims to explore the implementation of job training programs at PT Pos Indonesia (Persero) branch in Kediri a state-owned shipping company that must thrive in competition. The research adopts a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The findings reveal that the PT Pos Indonesia (Persero) Branch in Kediri has implemented various job training methods such as job instruction training, job rotation, classroom presentations, and learning, case studies, role-playing and behavior modeling, and mentoring. However, challenges were identified in the implementation of job training, including difficulties in online classroom learning due to system and network issues, and mentoring challenges caused by mentors who are not proficient in teaching or mentoring techniques. Recommended solutions include conducting thorough checks several days before training begins and the company considering scheduling specific training for mentors, such as Training of Trainers (ToT), to ensure expertise in subject matter and teaching techniques. All these recommendations are expected to optimize the benefits of job training implementation at PT Pos Indonesia (Persero) Branch in Kediri.